Pomen samopodobe bibliotekarja v komunikacijskem procesu - Kobal Grum, Darja (Knjižnica, 2004)
The article deals with the significance of the librarianćs self-concept in thecommunication process. First, it underlines the meaning of reference interviews, and second, it focuses on other micro and macro aspects of communication. The analysis shows that the librarianćs self-concept is hierarchically organised, structured, and therefore it consists of different areas. Each area equally contributes to the development and preservation of the appropriate librarianćs self-conceptč although some areas have more directinfluence than others. To attain a high self-concept, it is of fundamental importance, that the librarian develops all self-concept areas, from individual ones to social ones. It was found that a structured and positive specialistćs self-concept is highly significant for the contribution of effective reference interviews, and finally, the article offers some directions for a successful development of the communication process.
Keywords: samopodoba; komunikacija; bibliotekarji; referenčni pogovori